Construção e validação de um teste de conhecimento tático declarativo: processos de percepção e tomada de decisão no tênis - Layla Maria Campos Aburachid (2009)
The aim of the present study was to elaborate and validate a tactical declarative knowledge (TDK) test trough the process of perception and decision making in Tennis with evidences of content validity, criterion validity and indicate a construct validity, as well as checked if the theoretical analysis carried out by the experts in the process ofinternal validation corresponds to the reality of play situation (extern validation). Finally a comparison of the level of TDK by the categorical variables and suggestion of the form of test classification was the last objective in present study. A sample of 5 expert trainers from Minas Gerais, Rio de Janeiro and Sao Paulo States in theoretical validation phase and more 111 tennis players male and female, being 02 wheelchair professionals, 05 professionals, 12 amateur adults and 92 youth participated. The youth players subdivided in age categories: 12 years (14 tennis players), 14 years (33 tennis players), 16 years (33 tennis players) and 18 years (12 tennis players), belongs to main clubs and academies of Belo Horizonte, Sao Paulo and Angola (Africa), participants of the championship of Countries of Portuguese Language. The competitive level was classified in participation at state tournaments, national tournaments and international tournaments. Results considerations: a number of 39 items was validated by the contentvalidity coefficient (CVC), considering values above 0.80. This value was maintained for the proceedings of agreement between observers (CEO) and extern validity. After these proceedings 20 items were maintained for the consolidation of TDK test that allowed to elaborate a battery contained 10 items to maintained a mean duration at test applied in 25 minutes. The project pilot results: for the level of significance p 0,05, the level oftennis players TDK was not influenced by factors: club, age, category, year inside the category, participation in international tournaments, weekly trainings and duration of practice. There were significant differences of the level of TDK in the factors years of practice (p=0,024) and the experience in state tournaments (p=0,013) and nationaltournaments (p=0,050). The criterion validity through predictive validity presented relation between participation in state and national tournaments and the increase of the TDK level and it is an indicative that this validity also be confirmed at empirical proceedings.